Scientific Article Review on Practice of Organizational Leadership (Participative Leadership, Delegation and Empowerment) - Paulos Manedo Hafebo; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2024)
This paper assesses organizational leadership practice (participative leadership, delegation and empowerment) and its implication on organizational or employees’ performance. The study mainly focuses on theories of leadership that are directly attached to employees empowerment, employee participation and authority delegation in organizations. Besides this, in the scientific review writing on the topic a scholar reviewed methodologies employed, findings discovered and others issues in selected articles identified limitations. This identified limitations and gaps are recommended for further study on the topic. The study used a qualitative approach method and theory based as it discovered 16 published literature, books and researches review based on keywords from several theories of leadership, process of theory, and application of leadership theory. The study implicates the practice of organizational leadership theory; theories of empowerment and their practical implementation on organization need further research with respect to employees’ participation, employees’ empowerment and organizational efficiency.